Evolving Roles for International Social Work in Addressing Climate Change - Julie L. Nagoshi; Vijayan K. Pillai; Mashooq A. Salehin (Social Sciences)
Global warming and ozone layer depletion signal the onset of climate change, a “slow-onset” disaster exacerbating poverty and social inequality. Addressing this requires global cooperation, as exemplified by the United Nations’ Sustainable Development Goals (SDGs), particularly SDG 13, which focuses on climate action. Mitigation measures include reducing greenhouse gas emissions, transitioning to clean energy, and enhancing community resilience. Social workers play a crucial role in climate change adaptation, engaging in community resilience, advocacy, and policy influence. Their work spans individual counseling, social protection, and addressing environmental refugee crises. As climate change impacts intensify, social workers must expand their roles internationally, advocating for human rights, social justice, and disaster risk reduction. Human rights frameworks guide social workers in addressing climate-related health and social inequalities, emphasizing empowerment and equity. International social workers contribute significantly to disaster response, pandemic recovery, and community resilience, advocating for vulnerable populations and promoting sustainable development. Their evolving role underscores the need for a comprehensive, transnational approach to social protection, ensuring equitable access to resources and fostering a more just and resilient global community.